Clival defect in the pathogenesis of recurrent meningitis: a case report and literature review - Ahmet Naci Emecen; Reyhan Ertekin; Begumhan Baysal; Ferhat Arslan; Haluk Vahaboglu (Egyptian Journal of Neurosurgery, 2019)
Abstract Background Meningitis is a life-threatening infection often associated with high morbidity. Recurrent bacterial meningitis poses a clinical challenge, both clinically and diagnostically. To prevent further recurrences, the underlying causes of recurrent bacterial meningitis should be investigated intensively. Case presentation Here, we aim to present a patient referred to our clinic with rhinorrhea and found to the Staphylococcus aureus meningitis related to a clival defect. The patient reported no history of trauma, surgery, or brain neoplasm, and the cerebrospinal fluid leakage was classified as spontaneous. The patient had two episodes of meningitis in the last 4 years, but etiologic data of the previous episodes were absent. A pneumococcal vaccine was administered following her second attack, suggesting a possible Staphylococcus aureus infection due to altered colonization in the sinuses. She was successfully treated with linezolid but refused surgery to correct the defect and was discharged without neurologic sequelae. Conclusion Spontaneous cerebrospinal fluid leakage from the clivus which could provoke recurrent meningitis is a rare situation. In conjunction with appropriate rapid antibiotherapy for the prevention of recurrent meningitis, the removal of anatomical risk factors should be a principal aim. Effective surgical procedures prevent recurrences.